THE RELATIONSHIP OF THE ROLE OF CADRES AND THE VISIT OF THE ELDERLY IN PARTICIPATING THE POSYANDU FOR THE ELDERLY IN KEMENDUNG HAMLET, PENANGGUNGAN VILLAGE, TRAWAS DISTRICT, MOJOKERTO DISTRICT - triwibowo, heri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
The role of cadre holds a major role in running health services in posyandu to realize optimal health status, so that all activities conducted by cadre leads to the purpose and purpose of posyandu. The research aimed to know the relationship of role of cadres with elderly visit in follow elderly posyandu in Kemendung hamlet Penanggungan village, Trawas sub-district, Mojokerto regency. Research design used correlational analytics with cross sectional approach,The population of elderly people in Kemendung Hamlet aged 60-74 years of 120 elderly. Sampling technique used by means of Total Sampling to get a sample of 120 elderly. Data were collected using questionnaires instruments for cadre and KMS roles to find out elderly visits. Data analysis using cross tabulation.The result of the research shows that from 49 respondents who evaluated the role of positive cadres in their active visit were 24 respondents (49.0%) and from 71 respondents who assessed the role of negative cadres in the visit that never was 44 respondents (62.0%). It can be included that there is a relationship between the Relationship Role of Cadres with Elderly Visit to Elderly Posyandu In Dusun Kemendung Village Penanggungan District Trawas Mojokerto Regency. It is because the role of cadres can affect the liveliness of the posyandu elderly visit. The better the role of cadres in running posyandu, the higher the liveliness of visit in posyandu elderly.